Environmental Criticism in Kulah's Short Story Gus Tf Sakai's Work: An Overview of Ecocritics - Ahsani Taqwiem (Universitas Muhammadiyah Sidoarjo, 2020)
Literary work is not born from an empty thing. It was born from the results of human hands on the other hand interacting and absorbing many things from the complexity of the environment in which it lives. This explains how a literary work has an intimate relationship with nature. Literary ecology exists as a bridge to understand how nature is placed in a work. The object of this research is Kulah's short story written by Gus Tf Sakai. Kulah's short story contains a lot of environmental criticism that is very strongly illustrated. Through interpretation efforts and descriptions when approaching the data in the form of quotations of words or sentences taken in my short story. Ecological theory tries to explain how humans and nature influence each other as an ecosystem. Some of the environmental criticisms contained in kulah short story are criticisms of the deteriorating condition of the watershed which has resulted in many disasters such as floods, massive forest loss, and the dangers of waste which must be a concern for all parties. Efforts to prevent damage to nature must be taken in various ways including through the literary path. Environmental damage is the beginning for other disasters, therefore the effort to understand literature through natural perspectives becomes very important and crucial. Ecological’s point of view when reading literature are expected to be one of the educational solutions for readers in order to take part in protecting nature.